Human Monkeypox in People With HIV: Transmission, Clinical Features, and Outcome. (19th October 2022) - Vivancos-Gallego, María Jesús; Sánchez-Conde, Matilde; Rodríguez-Domínguez, Mario; Fernandez-Gonzalez, Pablo; Martínez-García, Laura; Garcia-Mouronte, Emilio; Martínez-Sanz, Javier; Moreno-Zamora, Ana María; Casado, Jose Luis; Ron, Raquel; Galán, Juan Carlos; Pérez-Elías, María Jesús; et al.
Abstract: We describe the first 25 persons with HIV diagnosed with human monkeypox virus (MPXV) in our hospital in an ongoing outbreak in Spain. Proctitis was the predominant finding in 52%, and MPXV DNA was detected in rectal swabs from 90%. Proctitis and demonstration of MPXV in rectal swabs support the sexual transmission of MPXV.